2017
DOI: 10.1038/tp.2016.264
|View full text |Cite
|
Sign up to set email alerts
|

Decreased hippocampal translocator protein (18 kDa) expression in alcohol dependence: a [11C]PBR28 PET study

Abstract: Repeated withdrawal from alcohol is clinically associated with progressive cognitive impairment. Microglial activation occurring during pre-clinical models of alcohol withdrawal is associated with learning deficits. We investigated whether there was microglial activation in recently detoxified alcohol-dependent patients (ADP), using [11C]PBR28 positron emission tomography (PET), selective for the 18kDa translocator protein (TSPO) highly expressed in activated microglia and astrocytes. We investigated the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 71 publications
3
54
3
Order By: Relevance
“…However, while a plethora of human and preclinical studies support TSPO as a glial marker, it is important to note that not all studies have detected TSPO upregulation in neuropathologies with a hypothesized inflammatory component. For instance, previous work showed no differences in TSPO PET signal in cocaine dependence (Narendran et al, 2014), and decreased signal in alcohol dependence (Hillmer et al, 2017; Kalk et al, 2017). In patients with psychosis, initial studies with first generation TSPO tracers showed an increase, whereas recent studies using second-generation radioligands are supportive of a decrease in TSPO levels (Plaven-Sigray et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…However, while a plethora of human and preclinical studies support TSPO as a glial marker, it is important to note that not all studies have detected TSPO upregulation in neuropathologies with a hypothesized inflammatory component. For instance, previous work showed no differences in TSPO PET signal in cocaine dependence (Narendran et al, 2014), and decreased signal in alcohol dependence (Hillmer et al, 2017; Kalk et al, 2017). In patients with psychosis, initial studies with first generation TSPO tracers showed an increase, whereas recent studies using second-generation radioligands are supportive of a decrease in TSPO levels (Plaven-Sigray et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…However, the author’s reported [ 11 C]PBR28 binding was unaffected among those subjects [143]. In the third study, Kalk et al[146] imaged 9 alcohol-dependent subjects approximately three weeks since their last drink (ad libitum cigarette smoking prior to scanning) and healthy controls. This [ 11 C]PBR28 study reported significantly lower TSPO availability (partial-volume corrected V T ) by 19% in the hippocampus relative to age-matched healthy controls, with similar trends in the midbrain, thalamus, ACC, and cerebellum.…”
Section: Resultsmentioning
confidence: 99%
“…This [ 11 C]PBR28 study reported significantly lower TSPO availability (partial-volume corrected V T ) by 19% in the hippocampus relative to age-matched healthy controls, with similar trends in the midbrain, thalamus, ACC, and cerebellum. On average, subjects were imaged 14 days since last benzodiazepine dose, and thus, benzodiazepines were unlikely to alter TSPO availability in this study [146]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations